THE IMPACTS OF COUNTRY-OF-ORIGIN, PRODUCT INVOLVEMENT, AND PRODUCT FAMILIARITY ON PRODUCT EVALUATION - Nugroho, Sahid Susilo; Rostiani, Rokhima; Gitosudarmo, Indriyo (Journal of Indonesian Economy and Business, 2014)
One of the most interesting phenomena in global business is the existence of a productâscountry-of-origin (COO). COO as an informational cue has been proven to affect consumerâspurchasing decisions in terms of their perception towards the productâs attributes as well astheir overall evaluation of the product. The objective of this study is to investigate the impacts ofcountry-of-origin on product evaluation in the Indonesian market by considering consumersâproduct familiarity and consumersâ product involvement. Consumersâ perception of theproductâs country-of-origin is assumed to have a significant influence on consumersâ considerationsin evaluating the product prior to purchase. This impact is supposedly moderated by theextent that consumers are familiar with the productâs attributes and to what extent the productis important and interesting to them. A survey design was employed to test the proposedlinkages among the variables.The target population of the survey was Indonesian consumers of imported products. Thesample unit is the person who has experience in buying or consuming foreign products. Thesample of 307 persons was drawn from Yogyakarta. This study examined televisions torepresent a high involvement product. The country stimuli are Korea and Indonesia . The studyapplied the regression analyses and hierarchical moderated regression to test the proposedhypotheses. The study found that: (1) Indonesian consumers associate positively a productâscountry-of-origin with their decision in evaluating the product for both Indonesian and Koreanproducts, (2) Indonesian consumers consider the level of economic development of the countryof-origin in evaluating the product, in which the effect of the country-of-origin is stronger for aKorean product than an Indonesian product, (3) Indonesian consumers with different levels ofproduct familiarity do not evaluate a product differently for both Indonesian and Koreanproducts, (4) Indonesian consumers with different levels of product involvement evaluate aKorean product differently.Keywords: country-of-origin, product evaluation, Korea, TV Product